Numerical optimization of a plasma wakefield acceleration experiment - K. V. Lotov; V. S. Tikhanovich (Physical Review Special Topics. Accelerators and Beams, 2007)
One possible way to demonstrate both the efficiency and beam quality in a plasma wakefield accelerator is to prepare matched drive and accelerated beams by removing a central slice from a single high-quality electron bunch (parent beam). For parameters of the parent beam given, the question arises how to maximize the number and energy of accelerated particles and minimize their energy spread and emittance. This question is addressed by numerical simulations. The optimum shape of the beams, required plasma length, achievable energy gain, and energy spread are found as functions of the plasma density and parent beam characteristics. The required control accuracy of adjustable beam and plasma parameters is determined.